Edukasi Preventif Covid-19 Melalui Media Digital di Universitas Cenderawasih Papua - Yos Wandik; Rif'iy Qomarullah; Kurdi Kurdi; I Putu Eka Wijaya Putra; Lestari Wulandari S; Muh Sawir (Journal of Dedicators Community, 2021)
Covid-19 preventive efforts were carried out in various ways and methods. One of them is using online digital media. The purpose of holding this activity is to find out what and how dangerous Covid 19 is with digital learning media. This activity uses a participatory method, using qualitative data and instruments. The science and technology targets in this activity are students of the Faculty of Sport Science (FIK), University of Cenderawasih Papua Indonesia in June 2020. The result of this service is that this activity is able to provide additional knowledge regarding the prevention and handling of Covid-19 and student enthusiasm because it is interactive. The Covid-19 Pandemic period had an impact, both positively and negatively. In terms of health, it is very detrimental, but for technological developments in the industrial era 4.0 this has an impact on the use of digital media facilities. Through the use of digital media, participants can understand and digest well that health promotion also needs attention. Furthermore, the benefits that can be obtained are the importance of maintaining a healthy lifestyle, maintaining cleanliness, and digital media that need to be used as much as possible in the era of technological disruption. Suggestions that can be given from this activity are: the community must adhere to health protocols and have awareness and willingness; healthy living.